Morphometric analyses of human dry tali of South Indian origin - Manjunath V. Motagi; Sugathan R. Kottapurath; Kavitarati Dharwadkar (Universiti Kebangsaan Malaysia, 2015)
Background: Talus is the key bone of the human body as it carries the whole weight of the body. Since the talus endures a lot of differential forces during locomotion, the stress patterns across the talus influence its overall dimensions. Research in skeletal biology and methodological approaches to the identification of human skeletal remains have advanced significantly in recent years. This study was undertaken because of the scarcity of the morphometric data in adult human dry tali of South Indian origin. Objectives: The objectives of this study were to estimate the angles of declination and inclination in adult human dry tali; to estimate the differences in the angles between right and left tali; and to report and estimate the differences in other morphological parameters such as maximum anterioposterior length of the talus, maximum transverse width of the talus, trochlear length, length of the sulcus tali, and width of the sulcus tali of right and left sides. Materials and Methods: The study was carried out on 50 (25 right and 25 left) adult dry tali of unknown ages and sexes over a period of 6 months in the Department of Anatomy, Amala Institute of Medical Sciences. The angles of declination and inclination were measured with goniometer. Other parameters were measured with digital Vernier calipers. Results: The mean angles of declination were 26° and 27° and those of inclination were 120° and 122° on the right and left sides, respectively. All the parameters measured showed no statistically significant difference between the right and left sides. Conclusion: The values of this study were relatively closer to the other studies. The parameters of this study may be helpful to surgeons, orthopedicians, and forensic anthropologists.